Building Design: An Integrated Framework - Khalifa, Giana Ibrahiem; Engdau, Shelly (Journal of Progress in Civil Engineering, 2025)
A green building is a clean, sustainable building, designed with natural materials, uses little energy and renewable ones at that, is easy to maintain and available at a reasonable cost. Reducing waste, pollution and harm to the environment. The term "green building" is used to describe buildings that are designed, constructed, and operated, to have a minimum impact on the environment, both indoor and outdoor. Green tech refers to the use of technology and science to minimize the environmental impact of human activity and protect the world's natural resources. This includes efforts in energy, agriculture, material science, atmospheric science, hydrology, and more. The discussions of indoor environment quality have not included many specific recommendations or criteria for building design, construction, or operation. Building projects described as green building demonstrations often make reference to indoor air quality, but these references are often general and qualitative. In addition, rating systems that have been developed to assess the "greenness" of a building are based largely on design features and are not particularly specific with respect to indoor air quality. This paper reviews the features of indoor air quality that are considered in green building discussions, demonstration projects, and rating systems. These green building features are discussed in terms of their completeness and specificity, and are compared to other guidance on building design, construction, and operation for good indoor air quality. A case study of indoor air quality performance in a green building is presented. This study includes a description of the indoor air quality features of the building and the results of a short-term indoor air quality evaluation of the building involving ventilation and contaminant concentration measurements. Green Building concept is the practice of creating structure using processes that are environmentally friendly and resources efficient during building life-cycle; selection of site, design, construction, operation, maintenance, renovation and destruction.